Contribution of Emotion Focused Coping Against Readiness For Natural Disasters - Syaiful Indra; Rizky Andana Pohan (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
Natural phenomena that hit parts of Aceh Province became a serious concern, fears of post-traumatic stress disorders experienced by children. Therefore, readiness to deal with natural disasters is considered important to be studied. Emotion focused coping is a cognitive process that focuses on reducing emotional stress and includes strategies such as, minimizing, avoiding, selective attention, positive comparisons, and taking positive and negative values from an event. This study aims to describe the emotion focused coping of Darul Abrar orphanage students in the readiness to deal with natural disasters. This study uses a quantitative approach. The study population was 595 orphanage students. The orphanage students sampled in this study were 240 people, selected by proportional random sampling technique. The instrument used is the Likert scale. The first, second and third research objectives were analyzed by percentage techniques, the fourth and fifth research objectives were analyzed by linear regression.Keywords: Emotion Focused Coping, Natural Disaster Preparedness, Orphanage